(untitled) (Conference on English Language Teaching, 2025)
This study aims to analyze the effectiveness of procedural text learning through vlog making and utilizing YouTube for grade IX students at SMP Negeri 1 Jeruklegi in 2025. The method used in this study is a qualitative descriptive method with an analytical approach. Data were obtained from project videos produced by students and also from learning reflections. The results of the study show that the innovations carried out can improve digital literacy, collaboration skills, and awareness of cultural matters. In current contextual learning, project-based learning for making vlogs turns out to be effective amidst the limited facilities owned by students.